A rehabilitation approach to the falls of geriatric patients - Marlena Kontowicz; Beniamin Szmelcer; Michał Wilczyński; Martyna Lamtych; Karolina Kubiak; Aneta Karło; Olga Rymarska; Klaudia Kwiatkowska; Patrycja Wszelaki; Małgorzata Gajos; Marta Podhorecka; Kornelia Kędziora Kornatowska (Kazimierz Wielki University, 2019)
Abstract: Background: Falls of the elderly are not only in themselves one of the most common problems of geriatric patients, but also the cause of many complications that affect permanently or for a shorter period of time affect the quality of life of people over 65 years of age. These changes affect not only the efficiency and motility of the elderly but also may reduce self-esteem, limit social life or cause loss of self-confidence. Material and methods: Analysis of available literature, articles in the Google Scholar database and PubMed using keywords: falls, geriatrics, aging process, problem Results: In clinical practice, many tests and scales are used to prevent the fall of older people and related complications. These include: Timed Up & Go (TUG), Tinetti scale, Dynamic Gait Index (DGI), One Leg Standing (OLS), Four Square Step Test (FSST), Berg test or Functional Reach (FR). Preventing falls can primarily be achieved by the use of appropriate rehabilitation methods, which include, among others, kinesitherapy and properly selected orthopedic equipment. The aim of individually selected kinesitherapy is to restore or maintain the patient's full fitness through the use of physical exercises to improve the balance, increasing mobility and efficiency. In the case of orthopedic supplies, the most common are baby walkers (without wheels, walker with wheels, using a triangular and quadrangular base) and orthopedic balls. Conclusions: Prophylaxis to prevent destructive effects of falls of geriatric patients should be carried out in a comprehensive manner and cover a wide range of activities. There is a further need for research and discussion on the effectiveness of forms of rehabilitation to prevent the falls of older people